Spin interactions in decorated graphene nanoflakes with two localized spin-1/2 entities - Toshikaze Kariyado (Materials Today Quantum)
Magnetic properties of graphene nanoflakes with designed edge shapes are theoretically analyzed by means of the first-principles calculation. As a starting point, we take a nanoflake with decorated zigzag edges where no magnetism is expected. Then, it is shown that removal of one decoration unit induces a well-defined localized spin-1/2 state. When two decoration units are removed, there arise two localized spin-1/2 states. Notably, when two spins are aligned in the same edge, the spin–spin interaction is ferromagnetic, while when two spins are aligned in the opposite edges, the spin–spin interaction is antiferromagnetic. This suggests that decorated nanoflakes form a promising playground for nanoscale spin devices with tunable spin–spin interactions by designing edge shapes.